Chemistry of Nanocontainers - Albrecht, Markus; Hahn, Ekkehardt; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
Stefan Kubik Molecular Cages and Capsules with Functionalized Inner Surfaces Bruno Therrien Drug Delivery by Water-Soluble Organometallic Cages Dariush Ajami Julius Rebek Reversibly Expanded Encapsulation Complexes A. Carina Schulze Iris M. Oppel Container Molecules Based on Imine Type Ligands Tobias Schröder Satya Narayan Sahu Jochen Mattay Molecular Capsules Derived from Resorcin[4]arenes by Metal-Coordination Rolf W. Saalfrank Andreas Scheurer Coronates, Spherical Containers, Bowl-Shaped Surfaces, Porous 1D-, 2D-, 3D-Metallo-Coordination Polymers, and Metallodendrimers
Keywords: Chemistry; Chemistry, Organic; Polymers; Nanochemistry; Chemistry; Organic Chemistry; Nanochemistry; Polymer Sciences